Women in Islamic Historiography and History - Saepudin, Didin; Zahra, Nabila Himmatina (JURNAL INDO-ISLAMIKA, 2022)
This article aims to reveal the rareness of historical writing that elevated the female figure as the main character. This gives rise to the assumptions that women are not much involved in history. The method used in this article is the historical research method. This Article finds that there are several possible factors that have made the writing of women's development history neglected and relatively slow compared to other social histories. First, the erroneous paradigm of women's history. Many opinions assume that everything related to women's problems is domestic issues and private. While anything related to science is identical to the world of men. Second, the wrong perspective about women's world is very influential on other factors. Among them are methodological and source issues; women are considered to be dealing with private issues only, while most of the documents/data deal with public issues, which are dominated by men's world. Therefore, it is possible that women are often overlooked and neglected from the record